Analisis Faktor- Faktor Yang Berpengaruh Terhadap Persediaan Bahan Baku Tandan Buah Segar di Pabrik Kelapa Sawit Cikasungka PT. Perkebunan Nusantara VIII Kabupaten Bogor Berdasarkan Persepsi Stakeholders - Nur Azizah Nasution; Slamet Abadi; I Putu Eka Wijaya (Jurnal Ilmiah Wahana Pendidikan, 2022)
Oil Palm Oilimportant in economic activity. PT. Oil palm plantation is one of the state-owned companies located in West Java. Companies must pay attention to the quality of raw materials and procurement of raw materials in order to achieve maximum production. Many factors can affect the failure to achieve raw material procurement, namely inadequate raw material sources, inadequate transportation, fluctuating raw material prices and a lot of competition. This study aims to determine the factors that influence the supply of palm oil raw materials based on the perception of stakeholders.sample was determined using the Slovin formula and the sample was taken using stratified random sampling. The analysis technique used is validity test, reliability test, classical assumption test and multiple linear regression. The results showed that 75.40% influence of the independent variable sources of raw materials, competition, raw material prices, transportation on the dependent variable raw material inventory. The results showed that the results of hypothesis testing simultaneously independent variables (source of raw materials, competition, raw material prices, transportation) simultaneously affected the dependent variable (raw material inventory). Partial test only variable source of raw materials that affect the supply of raw materials